2012
DOI: 10.4025/actasciagron.v34i2.12257
|View full text |Cite
|
Sign up to set email alerts
|

Activated charcoal and graphite for the micropropagation of Cattleya bicolor Lindl. and a orchid double-hybrid ‘BLC Pastoral Innocence’

Abstract: ABSTRACT.No previous studies have investigated the use of graphite instead of activated charcoal in orchids. In this work, different concentrations of activated charcoal or graphite were added to KC medium to darken the culture medium and stimulate the in vitro propagation of Cattleya bicolor and of a double hybrid orchid ('BLC Pastoral Innocence'). The seedlings were inoculated on growth regulator-free KC medium; the effects of activated charcoal (0.0, 1.5, 3.0, 4.5, 6.0, and 7.5 g L -1) and graphite (0.0, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
(2 reference statements)
1
8
0
Order By: Relevance
“…reported that apart from darkening the medium, activated charcoal is related to significant results concerning root growth of the plantlets (PRIZÃO et al, 2012). Dezan et al (2012), for example, found that the reduction in the salt concentration of MS culture medium was beneficial for the in vitro development of Schomburgkia gloriosa plantlets, as similarly found in this study with the same species.…”
Section: Resultssupporting
confidence: 80%
“…reported that apart from darkening the medium, activated charcoal is related to significant results concerning root growth of the plantlets (PRIZÃO et al, 2012). Dezan et al (2012), for example, found that the reduction in the salt concentration of MS culture medium was beneficial for the in vitro development of Schomburgkia gloriosa plantlets, as similarly found in this study with the same species.…”
Section: Resultssupporting
confidence: 80%
“…Species of the Cattleya genus and their hybrids are currently the most commercialized orchids in Brazil due to their large, colorful flowers (PRIZÃO et al, 2012). The asymbiotic cultivation of orchids can be used to reduce the effects of their predation in forests, to obtain in vitro germination of a large fraction of their seeds, and to make possible the re-establishment of these species in natural environments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in general activated charcoal presence was benefi cial for the development of the aerial part of the seedlings. PRIZÃO et al (2012) confi rmed that the presence of charcoal was particularly important in inducing roots and sprouts in the double hybrid of orchid 'BLC Pastoral Innocence' when inoculated in medium without growth regulator.…”
Section: Resultsmentioning
confidence: 89%
“…This shows that seedlings cultivated in the medium with higher salt availability and charcoal presence benefi ted in terms of growth parameters. PRIZÃO et al (2012) confi rmed that the use of activated charcoal is useful for root induction in seedlings of Cattleya bicolor.…”
Section: Resultsmentioning
confidence: 93%